Pemanfaatan Akun Instagram @Lpmunsika Sebagai Media Komunikasi dan Informasi Bagi Mahasiswa Universitas Singaperbangsa Karawang - Maylinda Rahmawati, Birty; Oky Oxcygentry; Tri Susanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Mass media as a medium of communication and information has had a major impacton people’s livesover time. The media can provide good news and convey it ini a good way. Postive news and information provided by the press media can encourage positive behavior from readers. The Singaperbangsa University Karawang student press agency is one of the news outlets that reports about campus, the latest news, education, tips and tricks in clear, concise, easy to understand and trustworthy language. The Singaperbangsa University Karawang student press organiation also uses Instagram as a platform to provide positive and informative news and information to the public, especially to Singaperbangsa University Karawang Student. Therefore, the perceptions of Singaperbangsa University Karawang Student who follow the @lpmunsika account is very necessary to understand the Singaperbangsa University Karawang Student Press intitution in sharing posituve news and information via Instagram. The research method used is a qualitative approach using desciptive methods. The theory used is the Technology Accetance Model Theory (TAM). The results that have been obtained from this research are that the Student Press Intitution at Singaperbangsa University Karawang in sharing news and information via Instagram can influence the perceptions and knowledge of followers especially student at Singaperbangsa University Karawang.